Temporal Variability in Electrocardiographic Indices in Subjects With Brugada Patterns - Lee, Sharen; Zhou, Jiandong; Liu, Tong; Letsas, Konstantinos P.; Hothi, Sandeep S.; Vassiliou, Vassilios S.; Li, Guoliang; Baranchuk, Adrian; Sy, Raymond W.; Chang, Dong; Zhang, Qingpeng; Tse, Gary (Frontiers in Physiology, 2020)
Background: Patients with Brugada electrocardiographic (ECG) patterns have differing levels of arrhythmic risk. We hypothesized that temporal variations in certain ECG markers may provide additional value for risk stratification. The present study evaluated the relationship between temporal variability of ECG markers and arrhythmic outcomes in patients with Brugada pattern ECG. Comparisons were made between low-risk asymptomatic subjects versus high-risk symptomatic patients with a history of syncope, ventricular tachycardia (VT) or ventricular fibrillation (VF). Methods: A total of 81 patients presenting with Brugada ECG patterns were recruited. Serial ECGs and electronic health records from January 2004 to April 2019 were analyzed. Temporal variability of QRS interval, J point-Tpeak interval (JTp), Tpeak-Tend interval (Tp-e) and ST elevation (STe) in precordial leads V1-3, in addition to RR-interval from lead II, was assessed using standard deviation and difference between maximum and minimum values over the serial ECGs. Results: Patients presenting with type 1 Brugada ECG pattern initially had significantly higher variability in JTp from lead V2 (SD: 33.5±13.8 vs. 25.2±11.5 ms, P=0.009; max-min: 98.6±46.2 vs. 78.3±47.6 ms, P=0.047) and STe in lead V1 (SD: 0.117±0.122 vs. 0.053±0.030 mV; P=0.004). Significantly higher variability in Tp-e interval measured from lead V3 was observed in the VT/VF group compared to the syncope and asymptomatic groups (SD: 20.5±8.5 vs. 16.6±7.3 and 14.7±9.8 ms; P=0.044; max-min: 70.2±28.9 vs. 56.3±29.0 and 43.5±28.5 ms; P=0.011). Conclusions: Temporal variability in ECG indices provides additional value for risk stratification in patients with Brugada pattern.